The Role Of OCCRP’s Soft Power In Framing President Joko Widodo Leadership On Corruption - Diqi Hadiq; Imam Mahdi (INJECT (Interdisciplinary Journal of Communication), 2025)
This research analyzes how the Organized Crime and Corruption Reporting Project (OCCRP), as a transnational actor, frames President Joko Widodo on the issue of corruption and its impact on domestic and international public perception. This research uses a qualitative approach with soft power analysis, framing theory, and boomerang pattern, examining transnational media strategies in constructing corruption narratives. The research results show that OCCRP uses soft power through investigations and voting to nominate Jokowi as a finalist for "Person of the Year in Organized Crime and Corruption," which triggers pressure on the government. Framing is carried out through problem definition, cause diagnosis (political dynasties, conflicts of interest, weakening of the KPK), moral judgment, and solution recommendations. The boomerang pattern shows how local media exploit international reports to criticize the government, trigger media polarization, and the media-power dynamics. OCCRP's soft power shapes public perception and has the potential to influence Indonesia's international reputation. This research contributes to understanding transnational media's role in shaping public perception, influencing domestic politics, and the importance of image in the global media era.